The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1073/pnas.76.12.6096
|View full text |Cite
|
Sign up to set email alerts
|

13C nuclear magnetic resonance studies of anaerobic glycolysis in suspensions of yeast cells.

Abstract: Anaerobic glycolysis in Saccharomyces cerevisiae has been studied by 13C NMR at 90. (7), was grown to one-fourth of saturation at 30°C in a liquid medium containing, per liter, 10 g of Bacto-peptone, 5 g of yeast extract, 4 g of (NH4)2SO4, 1 g of KH2PO4, 0.5 g of MgSO4, 0.5 g of CaC12, and 30 g of glucose.Prior to harvesting, the cultures were cooled to 5°C in icecold water with continuous shaking. Subsequently, the cells were collected by low-speed centrifugation at 4°C and washed twice in the ice-cold suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 22 publications
(19 reference statements)
2
49
0
1
Order By: Relevance
“…2B) [2,4] h-hydroxybutyrate [20]. Modeling with nonglucose substrates is complicated by the fact that, in contrast to glucose, the rate of uptake of 13 C-label into brain metabolism is dependent on the substrate concentration in the blood.…”
Section: Choice Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…2B) [2,4] h-hydroxybutyrate [20]. Modeling with nonglucose substrates is complicated by the fact that, in contrast to glucose, the rate of uptake of 13 C-label into brain metabolism is dependent on the substrate concentration in the blood.…”
Section: Choice Ofmentioning
confidence: 99%
“…The potential of 13 C NMR spectroscopy to study metabolic pathways was demonstrated using suspensions of microorganisms [1,2]. The first attempt to model the flow of 13 C label into the TCA cycle was made in 1983 by Chance et al [3] in the heart, at a time when such analysis required some of the fastest computers available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity and resolution of the method with respect to the chemical nature of cellular components renders it attractive for studies of cell physiology [ 8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose metabolism was the first to be examined with 13 C MRS experiments in yeast [118] and E. coli [122], the latter showing time courses of by-products related to glucose catabolism. Few years later a first attempt of modelling glucose uptake was made on data collected from yeast cells fed with [1e 13 C] and [6e 13 C] glucose with a Michaelis-Menten kinetic model [123], while main chemical reactions of the TCA cycle were estimated for the first time in cardiac tissue in vitro [11]. Up to this point, computational methods were still immature and magnetic fields available for research reached approximately 2 Tesla.…”
Section: Brain Mrs In Its Infancymentioning
confidence: 99%